Assessing the effect of predator control on an endangered goose population subjected to predator‐mediated food web dynamics. Issue 5 (19th February 2019) - Marolla, Filippo; Aarvak, Tomas; Øien, Ingar J.; Mellard, Jarad P.; Henden, John‐André; Hamel, Sandra; Stien, Audun; Tveraa, Torkild; Yoccoz, Nigel G.; Ims, Rolf A.
Abstract: Assessing the effectiveness of conservation actions to halt population declines is challenging when confounded by other factors. We assessed whether culling of red fox, a predator currently increasing in number in the sub‐Arctic, contributed to recent recovery of the critically endangered Fennoscandian population of Lesser White‐fronted Goose Anser erythropus, while controlling for potentially confounding food web dynamics. Using 19 years of data, 10 before and 9 after the implementation of annual red fox culling, we estimated the effect of this action on annual performance of the goose population. We corrected for the potentially confounding effects of cyclic rodent dynamics and semi‐domestic reindeer carrion abundance, both of which are expected to trigger predator functional and numerical responses, as well as for annual variation in spring phenology. Goose reproductive success fluctuated in synchrony with the rodent cycle and was negatively related to abundant carrion. When accounting for these aspects of food web dynamics, there was no evidence for an effect of red fox culling on reproductive success. There was, however, a tendency for fox culling to increase adult survival. Our analysis suggests that goose performance in their breeding area is influenced by fluctuating offspring predation, mediated by mainly natural (rodents) and partly anthropogenic (semi‐domestic reindeer) dynamic components of the food web. Synthesis and applications . The effect of a decade‐long red fox culling on goose reproductive success and survival is currently uncertain, despite predation driving reproductive success through changes in rodent and reindeer carrion abundance. New management actions may consist of regulation of reindeer herd sizes and/or removal of carcasses to reduce the subsidizing effect of reindeer carrion on mesopredators. Getting robust evidence regarding the impact of red fox culling on population recovery depends on continuing research to disentangle food web dynamics and efficiency of management actions. Abstract : The effect of a decade‐long red fox culling on goose reproductive success and survival is currently uncertain, despite predation driving reproductive success through changes in rodent and reindeer carrion abundance. New management actions may consist of regulation of reindeer herd sizes and/or removal of carcasses to reduce the subsidizing effect of reindeer carrion on mesopredators. Getting robust evidence regarding the impact of red fox culling on population recovery depends on continuing research to disentangle food web dynamics and efficiency of management actions.